Kazakh sports culture: theory and practice - et. al., Sapanov S.Zh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
T Important theoretical aspects are considered in this article: the origin and essence of the Kazakh controversial culture. Sport competitive culture is the only part of the general agonistics, which includes various other kinds of competitions: poetic, musical etc., and Kazakh controversial culture is a part of the universal human culture. The questions of sports culture and philosophy, especially its agonistic context, seem to be the most complex, interesting and relevant. However, deep theoretical development is required to understand the essence of agon in the world and national sports culture, as one of the most socially demanded and the most developed variety of culture. Agonistics as a cultural phenomenon attracts the attention of the world scientific community: culturologists, philosophers, art historians, economists, teachers, etc. We have taken the Kazakh example, the method of comparing the world's agon with the Kazakh tradition: its ancient sources, its national-specific characteristics, its organic connection with the initial bases: martial arts, rituals and sports games of ancient Turkic peoples to identify the essence, origin, forms of agon. Such a national-theoretical approach sheds light not only on the specifics, but also on the general laws of the development of a sport-competitive culture, on the common origins and the universal essence of adversarial (agon) in its various manifestations and not only sports. The article explores theoretical approaches, interpretations of foreign, Kazakh philosophers and culturologists. This scientific theoretical and methodological base is of fundamental importance for studying the essence and genesis of world sports and sports phenomena.